2010
DOI: 10.1111/j.1479-828x.2010.01140.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term follow‐up of women with gestational diabetes mellitus: The South Australian Gestational Diabetes Mellitus Recall Register

Abstract: Expansion of the GDM Recall Register is likely to result in increased opportunities for early detection of diabetes for this high-risk group in South Australia, therefore allowing earlier intervention and treatment to prevent or reduce serious, costly diabetes-related complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 10 publications
1
34
1
Order By: Relevance
“…Furthermore, the National Gestational Diabetes Register in Australia has shown that postpartum rates increase up to 73% with the implementation of a local register system for women with GDM. This system encompasses the provision of information for women on GDM diagnosis and sends postpartum reminders to patients [49]. A comparable system is present in the Northern part of Belgium, the project 'Sweet Pregnant' (www.zoetzwanger.be).…”
Section: Challenges To Organize the Postpartum Follow Upmentioning
confidence: 99%
“…Furthermore, the National Gestational Diabetes Register in Australia has shown that postpartum rates increase up to 73% with the implementation of a local register system for women with GDM. This system encompasses the provision of information for women on GDM diagnosis and sends postpartum reminders to patients [49]. A comparable system is present in the Northern part of Belgium, the project 'Sweet Pregnant' (www.zoetzwanger.be).…”
Section: Challenges To Organize the Postpartum Follow Upmentioning
confidence: 99%
“…In 2009, the scheme resulted in 56.3% of women on the register who returned the update form returning for postpartum screening [5]. A similar scheme in Ontario, Canada sends postal reminders to women and their doctors.…”
Section: Accepted Articlementioning
confidence: 99%
“…Self-reported rates of any blood glucose testing (not OGTT) increased from 56.3% to 75% with mailing of a second reminder letter. 35 Our results may not be transferrable to other jurisdictions. There is no limit or change in health care insurance for our women postpartum and many women take advantage of a one-year maternity leave policy.…”
Section: Discussionmentioning
confidence: 79%
“…Chittleborough et al (2010) examined diabetes screening rates over five years postpartum. 35 Study participants and their PCP's received an initial reminder letter at 15 months postpartum, and then a subsequent reminder letter every 12 months thereafter. Self-reported rates of any blood glucose testing (not OGTT) increased from 56.3% to 75% with mailing of a second reminder letter.…”
Section: Discussionmentioning
confidence: 99%